Tsunami Damage Assessment and Medical Triage - Mokhtari, Mohammad (IntechOpen, 2020)
This book is a collection of contributions from experts involved in tsunami study for the purpose of covering the different aspects from a tsunami at a local level, population health related to a tsunami disaster and early warning systems at a country level. The presented chapters, after being peer-reviewed, have been recommended to be accepted for publication. The content of the book consists of an introductory section that deals with the lessons learned from past tsunamis and today's practice; the monitoring of tsunami damage using the polarimetric microwave remote sensing technique, and considering the local tsunami on Pakistan's coast; the outbreak of devastating earthquakes; health consequences and medical provisions for the population and finally the risk of tsunamis in Mexico